Toxic Sublime: The Spectacle of Ecological Collapse in Contemporary Art - Gladys Putri; Bimala Putri; Henrietta Noir; Jujuk Maryati (Enigma in Cultural, 2025)
In the era of the Anthropocene, a significant genre of contemporary art has emerged that engages with ecological collapse by rendering environmental devastation visually captivating. This phenomenon, which this paper terms the "toxic sublime," presents a critical paradox: the aestheticization of catastrophe. This study investigates the visual and discursive strategies used by contemporary artists to represent ecological ruin and explores the complex ethical, political, and socio-economic implications of this practice. This study employed a qualitative, multi-modal critical approach. A purposively selected corpus of significant art projects created between 2015 and 2025 that address ecological degradation served as the primary data. The analytical methods included a visual semiotic analysis, operationalizing concepts from Barthes and Peirce to decode the aesthetic language of the artworks, and a Faircloughian critical discourse analysis of associated artist statements, interviews, and reviews. A heuristic modeling exercise, using a composite case study developed from real-world data, was also employed not to validate findings but to explore the generative logic of this aesthetic mode in a controlled, hypothetical context. The analysis identified a consistent taxonomy of aesthetic strategies central to the toxic sublime: 1) the strategic use of unnatural, hyper-saturated color to signify contamination; 2) the deployment of monumental scale to evoke awe and abstraction; and 3) the use of contaminated or synthetic materials as the artistic medium. The discourse analysis revealed a dominant framing of the artist as a "witness" or "alchemist" and the artwork as a "beautiful warning", which functions to legitimize the aestheticization process. In conclusion, the aestheticization of ecological collapse functions as a profoundly ambivalent cultural phenomenon. While it effectively captures attention, it risks neutralizing political urgency by transforming catastrophe into a consumable aesthetic object-a spectacle of decay. This study concludes that the toxic sublime is a defining aesthetic of the Anthropocene, but one that operates within the logic of the art market and the society of the spectacle. Its beautiful forms demand critical vigilance regarding art's complex role in an age of planetary crisis.